Crop Diversification in the Aral Sea Region: Long-Term Situation Analysis - Iroda Rustamova; Abdulla Primov; Aziz Karimov; Botir Khaitov; Akmal Karimov (Sustainability, 2023)
Agriculture contributes the most to the economy and provides agro-ecological benefits in the environmentally unsustainable Aral Sea region, but its productivity is steadily dropping. To improve the resilience of farming communities in the region, crop diversification is proposed to enable farmers to grow high-value competitive crops and obtain more stable farm incomes. This study provides long-term, multidisciplinary analyses and strategies for strengthening crop diversification amongst farmers in the Aral Sea region. The study analyzed data provided by the Ministry of Agriculture of the Republic of Uzbekistan and the statistical yearbook of 2000–2020. According to the gross margin study findings, farmers who use diversified cropping systems made considerably higher revenues than farmers relying on mono-cropping practices. This study demonstrates that greater crop diversity contributes to the rational use of natural resources and optimization plans, environmental sustainability, and food security as important natural and socio-economic issues in this region. The study findings suggest that proper crop diversification strategies need to be developed in the Aral Sea region to improve the sustainability of farming systems with enhanced resilience to devastating environmental and climate challenges.
Keywords: Q1; D13; D31; O18; 330; agriculture; Aral Sea; crop diversification; farmer's income; gross margin; Simpson's index; stress environment